CITY RESILIENCE STRATEGIES IN DEALING WITH THE AFTERMATH OF THE COVID-19 PANDEMIC: USING SOCIO-ECOLOGICAL SYSTEMS - Lailaturrohmah, Faizah; Fitrianto, Achmad Room (Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This study addresses the critical problem of urban vulnerability exposed by the Covid-19 pandemic, aiming to identify and evaluate effective resilience strategies within urban environments. Utilizing a qualitative descriptive methodology, this research draws on an extensive review of literature and environmental observations to analyze the strategies employed by cities in response to the pandemic. The study focuses on the socio-ecological systems approach, exploring how it can be applied to strengthen urban resilience. The findings reveal that resilience can be significantly enhanced through strategies that emphasize community engagement, adaptive governance, and the development of sustainable infrastructure. These insights provide valuable guidance for policymakers and urban planners in crafting resilient cities capable of withstanding future crises. The study concludes that a holistic, community-driven approach is essential for fostering urban resilience in the face of global challenges.